2021
DOI: 10.1017/s1352465821000497
|View full text |Cite
|
Sign up to set email alerts
|

Examining depression symptoms within OCD: the role of experiential avoidance

Abstract: Background: Obsessive compulsive disorder (OCD) and depression commonly co-occur. Past research has evaluated underlying mechanisms of depression in the context of other diagnoses, but few to no studies have done this within OCD. Aims: This study examines the relationships between distress tolerance (DT), experiential avoidance (EA), depression, and OCD symptom severity across intensive/residential treatment (IRT) for OCD. It was hypothesized that all variables would be significantly mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Thirdly, the negative effect of loneliness on depression is not only accounted by its role as a powerful stressor of a social nature, as previously suggested ( Hawkley & Cacioppo, 2010 ; Heinrich & Gullone, 2006 ), but also by impairing our ability to deal with stressing adverse events, in line with recent studies ( Hofmann & Hayes, 2019 ). In other words, it seems that loneliness increases the risk of a psychologically inflexible pattern of behavior characterized by seeking to avoid, scape, or control stressful thoughts and feelings despite their harmful consequences or at the expense of more effective and meaningful actions ( Bond et al, 2011 ; Browning, Van Kirk & Krompinger, 2021 ; Levin et al, 2014 ). Moreover, consistent with this interpretation, perceived stress also increases the risk of psychological inflexibility, enhancing the risk of depression; in other words, psychological inflexibility accounted for a significant part of the impact of perceived stress on depression.…”
Section: Discussionmentioning
confidence: 99%
“…Thirdly, the negative effect of loneliness on depression is not only accounted by its role as a powerful stressor of a social nature, as previously suggested ( Hawkley & Cacioppo, 2010 ; Heinrich & Gullone, 2006 ), but also by impairing our ability to deal with stressing adverse events, in line with recent studies ( Hofmann & Hayes, 2019 ). In other words, it seems that loneliness increases the risk of a psychologically inflexible pattern of behavior characterized by seeking to avoid, scape, or control stressful thoughts and feelings despite their harmful consequences or at the expense of more effective and meaningful actions ( Bond et al, 2011 ; Browning, Van Kirk & Krompinger, 2021 ; Levin et al, 2014 ). Moreover, consistent with this interpretation, perceived stress also increases the risk of psychological inflexibility, enhancing the risk of depression; in other words, psychological inflexibility accounted for a significant part of the impact of perceived stress on depression.…”
Section: Discussionmentioning
confidence: 99%
“…Unsurprisingly, interventions that reduce experiential avoidance also decrease depressive symptoms. Changes in experiential avoidance, for example, explained reductions in depressive symptoms following treatment for OCD (Browning et al, 2022). Similarly, experiential avoidance partly explained the effects of a mindfulness and self-compassion intervention on depressive symptoms (Yela et al, 2022), and another study (Zeifman et al, 2020) reported that decreases in avoidance following psychedelic use were related to lower depressive symptoms and suicidality.…”
Section: Choice Blindness With Clinical Outcomesmentioning
confidence: 99%
“…Overall, this indicates that sleep disturbance may aggravate OCS and impede its recovery, where interventions for sleep disturbance may decrease OCS. However, we should notice that higher OCD symptom severity were was significantly associated with more depressive symptoms in a clinical sample, so depression needs to be controlled when examining the relationship between sleep disturbance and OCS ( Browning et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%